Monitoring implementation of the convention on the Rights of Persons with Disabilities (CRPD) at national level: obligations on and options for Malaysia - Mokhtar, Khairil Azmin (Universitas Muhammadiyah Yogyakarta, 2017)
The Convention of the Rights of People with Disabilities is an international human rights treaty of the United Nations that has the objective to safeguard the rights and upheld the dignity of persons with disabilities. It was adopted on 13 December 2006. Malaysia ratified the Convention on 6 July 2010. Consequently, the country is obliged to fulfil obligations and duty under the convention. The Convention includes both national and international monitoring mechanisms. One of the obligations that Malaysia has to fulfil is to monitor the implementation of the Convention at the national level. Article 33 of the Convention requires the States set up national focal points governments in order to monitor implementation of the Convention’s precepts. States must also set up some sort of independent monitoring mechanisms. States also need to establish or designate a framework that includes one or more independent mechanisms to promote, protect and monitor the Convention’s implementation. After almost a decade of its adoption by the UN, and seven years after its ratification by Malaysia, it is pertinent to determine to what extent have the country managed to realize the spirit and to achieve the objective of the Convention. This is a qualitative and legal studies adopting doctrinal and legal research approaches. The focus of this paper is to outline obligations and duties of Malaysia under article 33 of the CRPD. It also examines whether the country has fulfilled the obligations and duties as well as outlining the current position on the matter. It also considers available options in fulfilling the obligations in monitoring the implementation of the Convention.